2014
DOI: 10.3122/jabfm.2014.01.130114
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated With Bone Mineral Density Screening in Adults With Intellectual Disabilities

Abstract: Background: Certain health characteristics place adults with intellectual disability at increased risk for osteoporosis. However, little data exist to describe how comorbid disease or medications affect screening patterns for these patients.Methods: We evaluated the relationship between bone density screening and the presence of risk factors using a secondary cross-sectional analysis of 5520 adults aged 19 years and older with the diagnosis of intellectual disability.Results: Of the sample, 22.9% received one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Those who lived at home were also more likely not to engage in DXA screening; however, this could possibly be because those at home were generally younger. Overall, levels of DXA scans were low, a finding similar to Dreyfus et al () who suggest the need for service provider awareness. Screening recommendations vary considerably, and there are no specific recommendations for people with ID in Ireland.…”
Section: Discussionsupporting
confidence: 77%
“…Those who lived at home were also more likely not to engage in DXA screening; however, this could possibly be because those at home were generally younger. Overall, levels of DXA scans were low, a finding similar to Dreyfus et al () who suggest the need for service provider awareness. Screening recommendations vary considerably, and there are no specific recommendations for people with ID in Ireland.…”
Section: Discussionsupporting
confidence: 77%
“…It is clearly shown that low bone mass in DS might emerge in early years and becomes a significant health problem when they become older. Despite the high prevalence of osteoporosis, persons with ID are less likely to receive BMD testing, potentially indicating barriers to screening at individual, organisational and policy levels (Dreyfus et al 2014). While screening for osteoporosis is generally recommended for women over 65 years old (US Preventive Services Task Force 2011), corresponding recommendation for persons with ID is not available because of the insufficient understanding of how BMD changes with age.…”
Section: Introductionmentioning
confidence: 99%
“…The causes and significance of sterile pyuria are unclear, yet it can confuse patient diagnosis and treatment. In addition, despite higher risks of fractures, Dreyfus et al 15 noted that bone mineral density testing is underused in adults with intellectual disability, especially those men and women with Down syndrome.…”
Section: Research By Family Physicians For Family Physicians Can Imprmentioning
confidence: 99%